The Routledge handbook of tourism marketing - McCabe, Scott (ed.) (Routledge, 2014)
"The Routledge Handbook of Tourism Marketing explores and critically evaluates the current debates and controversies inherent to the theoretical, methodological and practical processes of marketing within this complex and multi-sector industry. It brings together leading specialists from range of disciplinary backgrounds and geographical regions to provide reflection and empirical research on this complex relationship. The Handbook is divided in to nine inter-related sections: Part One deals with shifts in the context of marketing practice and our understanding of what constitutes value for tourists; Part Two explores macromarketing and tourism; Part Three deals with strategic issues; Part Four addresses recent advances in research; Part Five focuses on developments in tourist consumer behaviour; Part Six looks at micromarketing; Part Seven moves on to destination marketing and branding issues; Part Eight looks at the influence of technological change on Tourism Marketing and Part Nine explores future directions. This timely book offers the reader a comprehensive synthesis of this sub discipline, conveying the latest thinking and research. It will provide an invaluable resource for all those with an interest in tourism and marketing, encouraging dialogue across disciplinary boundaries and areas of study. This is essential reading for Tourism students, researchers and academics as well as those of Marketing, Business, Events Management and Hospitality Management"--